2007
DOI: 10.1105/tpc.107.054262
|View full text |Cite
|
Sign up to set email alerts
|

The Downy Mildew Effector Proteins ATR1 and ATR13 Promote Disease Susceptibility in Arabidopsis thaliana

Abstract: The downy mildew (Hyaloperonospora parasitica) effector proteins ATR1 and ATR13 trigger RPP1-Nd/WsB-and RPP13-Nddependent resistance, respectively, in Arabidopsis thaliana. To better understand the functions of these effectors during compatible and incompatible interactions of H. parasitica isolates on Arabidopsis accessions, we developed a novel delivery system using Pseudomonas syringae type III secretion via fusions of ATRs to the N terminus of the P. syringae effector protein, AvrRPS4. ATR1 and ATR13 both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
275
1
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(286 citation statements)
references
References 71 publications
8
275
1
2
Order By: Relevance
“…delivery of effectors from other strains, or even from oomycetes (20), can increase the virulence of WT strains. Here, we have learned additional properties of the DC3000 T3E repertoire in the context of interactions with N. benthamiana: (i) no single T3E is sufficient for significant virulence, (ii) some T3Es seem to interfere with an early phase of the plant immune response (i.e., by disrupting PAMP perception) such that other T3Es make a contribution to virulence only in their presence, (iii) early-acting effectors also seem to suppress defenses elicited by the T3SS machinery, (iv) T3Es in small groups with reduced redundancy can be observed to contribute in a hierarchical fashion to growth and symptom production, and (v) a minimal functional repertoire seems to require several effectors and members of at least two REGs.…”
Section: Discussionmentioning
confidence: 99%
“…delivery of effectors from other strains, or even from oomycetes (20), can increase the virulence of WT strains. Here, we have learned additional properties of the DC3000 T3E repertoire in the context of interactions with N. benthamiana: (i) no single T3E is sufficient for significant virulence, (ii) some T3Es seem to interfere with an early phase of the plant immune response (i.e., by disrupting PAMP perception) such that other T3Es make a contribution to virulence only in their presence, (iii) early-acting effectors also seem to suppress defenses elicited by the T3SS machinery, (iv) T3Es in small groups with reduced redundancy can be observed to contribute in a hierarchical fashion to growth and symptom production, and (v) a minimal functional repertoire seems to require several effectors and members of at least two REGs.…”
Section: Discussionmentioning
confidence: 99%
“…Stable effector expression in planta allows us to test whether the ectopic expression of a given effector affects plant susceptibility toward the corresponding pathogen (Bozkurt et al 2011;Fabro et al 2011;Caillaud et al 2012) or even other pathogens (van Esse et al 2008;Hewezi et al 2010;Bouwmeester et al 2011;Fabro et al 2011). Using this approach, effectors from Hpa, including ATR13, were shown to suppress plant defenses, notably PAMP-induced ROS burst and callose deposition, which are typical indicators of plant immune response activation (Sohn et al 2007;Fabro et al 2011).…”
Section: Nuclear-harxls Give Various Developmental Phenotypes When Exmentioning
confidence: 99%
“…Using this EDV system, Sohn et al (2007) have shown that Hpa effectors ATR1 and ATR13 confer enhanced virulence to the bacterial pathogen Pst DC3000. Kemen et al (2011) showed with this method that several classes of Albugo laibachii effectors conferred enhanced virulence to Pst DC3000.…”
mentioning
confidence: 99%
See 2 more Smart Citations